Pengaruh Senam Ergonomik Terhadap Tekanan Darah Lansia Penderita Hipertensi di Kelurahan Gayam Kabupaten Sukoharjo - Nur Rohmanni Yuliana; Riyani Wulandari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Hypertension is a major health problem among the elderly and a significant risk factor for cardiovascular disease. In Central Java, the prevalence of hypertension among the elderly ranked the highest in Indonesia in 2021 at 32.5%, and by 2024, it had markedly increased to 71.47%. This alarming rise highlights the urgent need for effective and practical interventions that can be implemented at the community level. One non-pharmacological intervention that has been shown to help lower blood pressure is ergonomic exercise, a form of physical activity designed to be safe, low-impact, and suitable for older adults. This study aimed to determine the effect of ergonomic exercise on the blood pressure of elderly individuals with hypertension in Gayam Village, Sukoharjo Regency. This research employed a quantitative, pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 17 elderly respondents selected through purposive sampling. Blood pressure measurements were obtained using a sphygmomanometer. The ergonomic exercise intervention was administered three times per week, with each session lasting 23 minutes, over a set intervention period. Data were analyzed using the Wilcoxon signed-rank test to assess differences in systolic and diastolic blood pressure before and after the intervention. The analysis revealed a p-value of 0.000 (p < 0.05), indicating a statistically significant reduction in blood pressure following the exercise program. These findings suggest that ergonomic exercise can effectively reduce blood pressure in elderly individuals with hypertension and may serve as a supportive, low-cost, and easily implemented intervention in community health programs. It is recommended that ergonomic exercise be incorporated into routine elderly health promotion activities to help control hypertension and improve overall cardiovascular health.